Electrospun Carbon/CuxO Nanocomposite material as Sustainable and High Performance Anode for Lithium‐Ion Batteries. Issue 6 (26th June 2019) - Maroni, Fabio; Bruni, Pantaleone; Giuli, Gabriele; Brutti, S.; Croce, Fausto
Abstract: The increase in energy density of the next generation of battery materials to meet the new challenges of the electrical vehicles era calls for innovative and easily scalable materials with sustainable processes. An innovative Cu x O/C nanocomposite material, characterized by a highly conductive 3D‐framework, with Cu x O/Cu‐metal contiguous nanodomains is prepared by electrospinning. The electrode processing is made using a polyacrylic acid binder. The nanocomposite has been fully characterized and the electrochemical performance shows high specific capacity values over 450 galvanostatic cycles at 500 mAg −1 specific current with capacity retention values over 80 %. In addition, the composite shows remarkable high rate performance and highly stable interface, which has been studied by impedance spectroscopy. Abstract : Improving the performance ! Highly conductive copper nanocrystalline domains are prepared in a nanocomposite material, with remarkable electrochemical cycling performance in a lithium battery. Galvanostatic cycling experiments show high specific capacities over 450 cycles at 500 mAg −1 specific current with a capacity retention of 80 %.